PENGARUH CITRA MEREK, KUALITAS PRODUK DAN E-WOM TERHADAP KEPUTUSAN PEMBELIAN SKINCARE EMINA PADA MARKETPLACE TOKOPEDIA DI KOTA BATAM - Saragi, Celine Angela; Hikmah, Hikmah (SCIENTIA JOURNAL, 2025)
This study investigates the impact of brand image, product quality, and electronic word-of-mouth (E-WOM) on purchasing decisions of Emina skincare products through Tokopedia marketplace in Batam City. The rapid growth of the beauty industry in Indonesia's e-commerce sector, particularly in skincare products, has made it essential to understand the factors influencing consumer purchasing behavior. Using a quantitative research approach, data was collected from 204 respondents through online questionnaires utilizing Likert scale measurements. The study employed purposive sampling method and multiple linear regression analysis to examine the relationships between variables. The findings revealed that brand image, product quality, and E-WOM each demonstrated positive and significant effects on purchasing decisions of Emina skincare products. These results provide valuable insights for skincare brands and e-commerce platforms to enhance their marketing strategies, particularly in building strong brand presence, maintaining product quality, and leveraging E-WOM effectively in the digital marketplace environment.